ANALISIS REAKSI HARGA SAHAM DAN VOLUME PERDAGANGAN ATAS PENGUMUMAN DIVIDEN KAS (Studi Empiris pada Perusahaan yang Listing di Bursa Efek Indonesia Tahun 2013 - 2015) - Aprilia, Yoga Gigih; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2017)
This research aims to analyse then influence cash dividend announcemet to abnormal return, cumulative abnormal return, dan trading volume activity before and after cash dividend announcement. Period of research which used from 2013 – 2015.The research type is even study method. Research population used all company which listed in Indonesia Stock Exchange. Technique of choosing sample is used purposive sample and get 67 company from 234 even study cash dividend announcement. The data used in this research obtained from website KSEI, website BEI, Online Trading System of Mirae Asset Sekuritas. The determination of return is using market adjusted model. Analyze technique used parametic test which using to examine hyposthesis in this research is statictic descriptive, normality test, one sample t-test and paired sample t-test.The result of the research are : (1) Cash dividend anncouncement not affect to abnormal return, it means there is no significant difference in average abnormal return between before and after the announcement of cash dividend. (2) Dividend announcement is affect to cumulative abnormal return, it means there is a difference in average cumulative abnormal return that is significant between before and after the announcement of cash dividend. (3) Dividend announcement is not affect to trading volume activity, it means there is no significant difference in average abnormal return between before and after the announcement of cash dividend.